2017
DOI: 10.1371/journal.pone.0169435
|View full text |Cite
|
Sign up to set email alerts
|

What Do Men Want from a Health Screening Mobile App? A Qualitative Study

Abstract: There is a lack of mobile app which aims to improve health screening uptake developed for men. As part of the study to develop an effective mobile app to increase health screening uptake in men, we conducted a needs assessment to find out what do men want from a health screening mobile app. In-depth interviews and focus group discussions were conducted with 31 men from a banking institution in Kuala Lumpur. The participants were purposely sampled according to their job position, age, ethnicity and screening st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 45 publications
6
19
0
1
Order By: Relevance
“…For the signs of addiction, the result suggested that the best practice was to include the information in a highlighted sub-section under the "possible side effect" section. This finding is meaningful since the easiness to read is relevant to patient education and users' willingness to read [55]. However, if this is used as the standard, then only 21% of collected PILs of OTC codeine met the criterion.…”
Section: Discussionmentioning
confidence: 89%
“…For the signs of addiction, the result suggested that the best practice was to include the information in a highlighted sub-section under the "possible side effect" section. This finding is meaningful since the easiness to read is relevant to patient education and users' willingness to read [55]. However, if this is used as the standard, then only 21% of collected PILs of OTC codeine met the criterion.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, physical activity, also associated with healthy eating and habits, 19 plays an important role as a preventive and protective factor of physical, psychological and sexual aspects. 10,16,22,25 The advancement of technology has contributed to the creation of applications aimed at the health and well-being of people. In a study conducted with the male population less likely to seek health services and obtain information through apps, men of different ages, ethnicities and occupations said that an optimal health screening application should have functions to directly measure and evaluate their health status.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that such an application should be reliable, should protect personal information, especially medical data, should contain updated information, and should be created by government or health care entities. 25 The use of health applications become friendly due to elements intrinsic to this new technology, such as accessibility, mobility and the continuous J Nurs UFPE on line. 2019;13:e240740 https://doi.org/ 10.5205/1981-8963.2019.240740 ability to transmit information, often in real time, in addition to bringing multimedia elements and geolocation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Todo lo anterior es relevante cuando se relaciona con el interés de los pacientes acerca de incluir la función de información nueva en una aplicación para DM2. Además, esta perspectiva de contenido de información en una app fue también mencionada por los participantes de un estudio en el que se quería indagar sus necesidades y deseos en cuanto al diseño de una app para el monitoreo de la salud masculina (25).…”
Section: Discussionunclassified